On Binomial Set-Theoretic Complete Intersections in Characteristic p - Barile, Margherita (Revista Matemática Complutense, 2008)
Using arithmetic conditions on a_ne semigroups we prove that for a simplicial toric variety of codimension 2 the property of being a set-theoretic complete intersection on binomials in characteristic p holds either for all primes p, or for no prime p, or for exactly one prime p.